EFFORTS TO IMPROVE STUDENT COOPERATION IN MATHEMATICS LEARNING USING NUMBER HEAD TOGETHER TYPE COOPERATIVE MODELS IN CLASS VII A STUDENTS OF SMP NEGERI 13 YOGYAKARTA - Novita Dewi Kurnia; Uswatun Khasanah (Universitas Ahmad Dahlan, 2017)
Fewer students cooperate at the time of learning. That is indicated by the condition of learning in the classroom. The response of students who aren’t entirely at the time given task. The participants are less active, application of cooperative Number Head Together mode and this type is expected to improved student cooperation. The research aims to improve cooperation between students and mathematics learning to use cooperative learning type Number Head together mode. This research is an action research class consisting of two cycles. The subject of the research is VII A grade student of 1st semester of the academic year 2016/2017 at SMP Negeri 13 Yogyakarta. The object of this research is the efforts to improve students collaboration in learning mathematics. Technic to collecting data is observation and interview. The instrument of the research is the collaboration students observation sheet. Teacher interview activity sheet, and student interview sheet. The category to succeed in the research is marked with increasing approximately the percentage of students teamwork minimal 61%. The result of the research is shown by cooperative learning mode we called if type Number Head Together mode. It can increase the student's teamwork in a mathematic lesson in VII A class. We can see from the result of the average percentage who shows that the increase in each cycle. The first cycle is 41,01%, enough to achieve this criteria and the second cycle is 65,05 % it achieves good criteria.